Organizational socialization in team sport environments - Benson, A. J.; Evans, M. B.; Eys, M. A. (Scandinavian Journal of Medicine & Science in Sports, 2016)
Socialization tactics are often used to manage initial group member interactions in a way that facilitates transition experiences. Although this process is heavily researched in organizational contexts, we sought to extend this line of inquiry to sport by examining the nature of socialization tactics used to integrate new members into existing teams. Interviews were conducted with 12 coaches and 12 athletes from several Canadian Interuniversity Sport teams to explore the nature of socialization and the circumstances underscoring why certain approaches are taken over others. A key process involved establishing congruency of role expectations between incoming athletes and group leaders, and socialization processes balanced expectations of conformity with encouragement of individual personalities within the group. A conceptual basis to examine socialization into team sport environments is discussed in relation to the extant organizational theories, and the practical implications of delineating sport socialization tactics are forwarded.